Solve for m... 


Expert Answers

An illustration of the letter 'A' in a speech bubbles

In order to solve this equation for m, we need to use the logarithmic rules to get m to be on one side of the equation and everything else on the other side:

`-2log_2(-8m-1)=0`   use power rule

`log_2(-8m-1)^{-2}=0`   switch to exponential form

`(-8m-1)^{-2}=2^0`   simplify each side

`1/(-8m-1)^2=1`   cross-multiply

`1=(-8m-1)^2`   simplify inside brackets (since squared)

`1=(8m+1)^2`   take square roots of each side

`+-1=8m+1`   simplify

`+-1-1=8m`   divide

`m=0`   or   `m=-1/4`   

Now sub back into the original equation and we see that m=0 is not a valid solution.

The solution to the equation is `m=-1/4` .

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial